Declining responsiveness of plasmodium falciparum infections to artemisinin-based combination treatments on the Kenyan coast - Borrmann, Steffen; Sasi, Philip; Mwai, Leah; Bashraheil, Mahfudh; Abdallah, Ahmed; Muriithi, Steven; Frühauf, Henrike; Schaub, Barbara; Pfeil, Johannes; Peshu, Judy; Hanpithakpong, Warunee; Rippert, Anja; et al. (PLOS ONE, 2011)
Background The emergence of artemisinin-resistant P. falciparum malaria in South-East Asia highlights the need for continued global surveillance of the efficacy of artemisinin-based combination therapies. Methods On the Kenyan coast we studied the treatment responses in 474 children 6-59 months old with uncomplicated P. falciparum malaria in a randomized controlled trial of dihydroartemisinin-piperaquine vs. artemether-lumefantrine from 2005 to 2008. (ISRCTN88705995) Results The proportion of patients with residual parasitemia on day 1 rose from 55% in 2005-2006 to 87% in 2007-2008 (odds ratio, 5.4, 95%CI, 2.7-11.1; P<0.001) and from 81% to 95% (OR, 4.1, 95%CI, 1.7-9.9; P = 0.002) in the DHA-PPQ and AM-LM groups, respectively. In parallel, Kaplan-Meier estimated risks of apparent recrudescent infection by day 84 increased from 7% to 14% (P = 0.1) and from 6% to 15% (P = 0.05) with DHA-PPQ and AM-LM, respectively. Coinciding with decreasing transmission in the study area, clinical tolerance to parasitemia (defined as absence of fever) declined between 2005-2006 and 2007-2008 (OR body temperature >37.5°C, 2.8, 1.9-4.1; P<0.001). Neither in vitro sensitivity of parasites to DHA nor levels of antibodies against parasite extract accounted for parasite clearance rates or changes thereof. Conclusions The significant, albeit small, decline through time of parasitological response rates to treatment with ACTs may be due to the emergence of parasites with reduced drug sensitivity, to the coincident reduction in population-level clinical immunity, or both. Maintaining the efficacy of artemisinin-based therapy in Africa would benefit from a better understanding of the mechanisms underlying reduced parasite clearance rates. Trial Registration Controlled-Trials.com ISRCTN88705995